DESCRIPTIVE READING MATERIALS FOR TENTH GRADERS: PALEMBANG TOURIST DESTINATIONS - Kananda Agustina Checaria; Ismail Petrus; Rita Inderawati (University of Kuningan, 2021)
The purpose of this study was to find out the validity, practicality and potential effect of the developed descriptive reading materials about Palembang tourist destinations for the tenth-graders of vocational high school¬. This study was conducted based on Akker (analysis, design, evaluation, and revision) development research design. The formative evaluation was consisted of self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field trial. Formative evaluation was intended to find out the validity, practicality and potential effect of the product. The average validity score of the developed product was categorized as a very highly valid level. The practicality in one-to-one was at a highly practical level and small group evaluation was at a very high practical level. The reading test material was categorized as effective. It showed that in the reading test students exceeded the passing grade which was 75. In brief, descriptive reading texts of Palembang tourist destinations were able to help students know about tourist destinations. The developed product was appropriate for the tenth-graders of vocational high school, especially for tourism majoring.